(untitled) (Indian Journal of Animal Production and Management, 2024)
Buffaloes have higher milking temperament scores than crossbred cows and therefore pose problems for proper milk let-down and efficient milk removal specially in machine milking. Their alveolar fraction of milk is relatively higher and cisternal fraction of milk is lower. The animals with small cisterns are more susceptible to the short-term autocrine inhibition of milk secretion in the mammary gland. For mechanization of milking in buffaloes they need to be conditioned to machine milking for appropriate milk ejection in the milking parlour for a period of about one week. For better milk ejection in buffaloes and to avoid dry running a special arrangement to the milking machine (DualVac arrangement- double vacuum arrangement) has been suggested as a possible solution.